1997
DOI: 10.1111/j.1365-2621.1997.tb04398.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Quality of Frankfurters Containing Oat Bran and Added Water

Abstract: Chicken frankfurters fat content was decreased by using various levels of oat bran and added water and evaluated for quality. Frankfurters with higher levels of oat bran had less expressible moisture and required higher shear stress to break. There were no difference in springiness among frankfurters made with different levels of oat bran; however, those with higher oat bran were rated less juicy and more grainy by taste panelists. The addition of water increased intensities of strain, springiness and juicines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 13 publications
5
58
1
7
Order By: Relevance
“…The reduction in the hardness value could be attributed to the softening in the connective tissue caused by the conversion of collagen to gelatin which improved meat tenderness [Dhanapal et increased due to starch gelatinization during the cooking process. As well, chicken sausage with a high water content (>50%) had lower shear stress and hardness, this result was also confi rmed by Chang & Carpenter [1997].…”
Section: Kinetic Data For Texture During Cooking Conditionssupporting
confidence: 69%
“…The reduction in the hardness value could be attributed to the softening in the connective tissue caused by the conversion of collagen to gelatin which improved meat tenderness [Dhanapal et increased due to starch gelatinization during the cooking process. As well, chicken sausage with a high water content (>50%) had lower shear stress and hardness, this result was also confi rmed by Chang & Carpenter [1997].…”
Section: Kinetic Data For Texture During Cooking Conditionssupporting
confidence: 69%
“…Incorporation of wheat and oat bran increased the shear press values. Higher shear press value of oat bran added frankfurters and wheat bran added burgers has been report- ed by Chang and Carpenter (1997) and Mansour and Khalil (1999), respectively. Sensory scores of bran added patties: Incorporation of wheat and oat bran decreased scores of all sensory attributes progressively as the level increased both in steamed and baked patties (Table 5).…”
Section: Resultsmentioning
confidence: 94%
“…whey powder affect the color of low fat products (Chang and Carpenter, 1997;Hughes et al, 1996;Serdaroðlu, 2006). The latter study reported that whey power can produce a lighter colored low-fat meatball.…”
mentioning
confidence: 86%